2013
DOI: 10.4028/www.scientific.net/aef.10.77
|View full text |Cite
|
Sign up to set email alerts
|

Alertness, Visual Comfort, Subjective Preference and Task Performance Assessment under Three Different Light's Colour Temperature among Office Workers

Abstract: Different CCT provided by different lighting are important in affecting human beings psychologically and physiologically, as well as visual and non-visual processes. This study aim in finding out the effects of warm white (WW) light (CCT=2700K), cool white (CW) light (CCT=4000K) and artificial Daylight (CCT=6200K) on worker's alertness, visual comfort level, preferences and task performance. A repeated measure experimental study was conducted among 46 office workers under controlled environment. Alertness leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
(11 reference statements)
1
4
0
Order By: Relevance
“…Alertness and arousal are known to affect cognitive performance . Previous studies also showed that better work performance was found along with enhanced alertness under high CCT lighting condition with more blue components, which aligns with our finding. These nonimage forming effects of blue light are mainly regulated by melanopsin illuminance .…”
Section: Discussionsupporting
confidence: 92%
“…Alertness and arousal are known to affect cognitive performance . Previous studies also showed that better work performance was found along with enhanced alertness under high CCT lighting condition with more blue components, which aligns with our finding. These nonimage forming effects of blue light are mainly regulated by melanopsin illuminance .…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the observed better visual comfort during dayLED per se could have led to better alertness and mood particularly in the morning and evening hours. This corroborates a finding by Shamsul et al ., 56 who tested three different colour temperatures (2700, 4000 and 6200 K all at 400 lux) in a workplace setup in the laboratory and found better typing performance along with more alertness and visual comfort under both the 4000 and 6700 K condition compared to the 2700 K condition.…”
Section: Discussionmentioning
confidence: 99%
“…Subjective alertness levels are certainly not only driven by environmental light (for a review see Cajochen et al 55 ) but also influenced by subjective aspects such as wellbeing 47 and visual comfort. 56 The influence of visual comfort on eye strain and fatigue has been recognized in research on recommendations of comfortable visual display terminal workstation design -an important aspect of visual ergonomics. 57 This needs to be extended into studies looking at the interplay between the visual and non-visual effects of lighting solutions on human cognitive performance and sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in circadian rhythms have also been associated with sleep quality and alertness in addition to mood and cognitive performance ( Garbarino et al, 2020 ). The Karolinska Sleepiness Scale (KSS) has been mainly used to measure both subjective sleepiness and alertness ( Shamsul et al, 2013 ; Chinazzo et al, 2019 ). Tools such as the Horne and Ostberg Morningness-Eveningness Questionnaire and the Munich Chronotype Questionnaire have also been used to assess the sleep quality of participants grouped according to their sleep–wake behaviour (morningness–eveningness; Jaeggi and Jaeggi, 2011 ; Adamsson et al, 2018 ).…”
Section: The Human Response To Daylight: Evaluation Methodsmentioning
confidence: 99%